2010
DOI: 10.1007/s12665-010-0832-8
|View full text |Cite
|
Sign up to set email alerts
|

The dispersion of fibrous amphiboles by glacial processes in the area surrounding Libby, Montana, USA

Abstract: Mining operations began at a world-class vermiculite deposit at Vermiculite Mountain near Libby,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Much of this watershed was subjected to the extreme conditions associated with the repeated, catastrophic drainage of Glacial Lake Missoula, but Glacial Lake Columbia persisted for some time after the last of these floods (Balbas et al 2017). As the Purcell trench lobe of the Cordilleran ice sheet receded, it would have exposed the lower Kootenai River valley but blocked drainage to the north, diverting streams from that area through the trench cut by the Purcell lobe and connecting the lower Kootenai and Pend Oreille basins (Langer et al 2011). Another connection between these basins appears to have existed at the low divide between the Bull River (lower Clark Fork) and Bull Lake (lower Kootenai) in Montana (Langer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this watershed was subjected to the extreme conditions associated with the repeated, catastrophic drainage of Glacial Lake Missoula, but Glacial Lake Columbia persisted for some time after the last of these floods (Balbas et al 2017). As the Purcell trench lobe of the Cordilleran ice sheet receded, it would have exposed the lower Kootenai River valley but blocked drainage to the north, diverting streams from that area through the trench cut by the Purcell lobe and connecting the lower Kootenai and Pend Oreille basins (Langer et al 2011). Another connection between these basins appears to have existed at the low divide between the Bull River (lower Clark Fork) and Bull Lake (lower Kootenai) in Montana (Langer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As the Purcell trench lobe of the Cordilleran ice sheet receded, it would have exposed the lower Kootenai River valley but blocked drainage to the north, diverting streams from that area through the trench cut by the Purcell lobe and connecting the lower Kootenai and Pend Oreille basins (Langer et al 2011). Another connection between these basins appears to have existed at the low divide between the Bull River (lower Clark Fork) and Bull Lake (lower Kootenai) in Montana (Langer et al 2011). Each of these connections would have provided access to fish originating from the Spokane River basin, which may have culminated in their reaching the Fraser River basin via the succession of glacial lakes trailing the receding ice sheet.…”
Section: Discussionmentioning
confidence: 99%
“…Between about 1920 and 1990, the Libby mine was a major source of vermiculite ore for the United States and for the world. (2) Numerous studies of workers from the Libby mine have demonstrated increased morbidity and mortality due to malignant and non-malignant diseases associated with exposure to LA. (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Increased risk for the development of mesothelioma among manufacturing workers who expanded and processed Libby vermiculite has been reported, (15) as has increased morbidity in workers from an Ohio facility that used Libby vermiculite in the manufacturing of lawn care and other agricultural products.…”
Section: Introductionmentioning
confidence: 99%